Gas-sensing features of nanostructured tellurium thin films - Tsiulyanu, Dumitru (Beilstein Journal of Nanotechnology, 2020)
Nanocrystalline and amorphous nanostructured tellurium (Te) thin films were grown and their gas-sensing properties were investigated at different operating temperatures with respect to scanning electron microscopy and X-ray diffraction analyses. It was shown that both types of films interacted with nitrogen dioxide, which resulted in a decrease of electrical conductivity. The gas sensitivity, as well as the response and recovery times, differed between these two nanostructured films. It is worth mentioning that these properties also depend on the operating temperature and the applied gas concentration on the films. An increase in the operating temperature decreased not only the response and recovery times but also the gas sensitivity of the nanocrystalline films. This shortcoming could be solved by using the amorphous nanostructured Te films which, even at 22 °C, exhibited higher gas sensitivity and shorter response and recovery times by more than one order of magnitude in comparison to the nanocrystalline Te films. These results were interpreted in terms of an increase in disorder (amorphization), leading to an increase in the surface chemical activity of chalcogenides, as well as an increase in the active surface area due to substrate porosity.
Keywords: gas-sensing properties; NO2; tellurium thin films; nanocrystalline films

Nanotechnological Basis for Advanced Sensors. NATO Science for Peace and Security Series B: Physics and Biophysics - Tsiulyanu, D. (Tellurium Thin Films in Sensor Technology, 2011)

(untitled) - He, Z.; Yang, Y.; Liu, J.-W.; Yu, S.-H. (Chem. Soc. Rev., 2017)

(untitled) - Ba, L. A.; Döring, M.; Jamier, V.; Jacob, C. (Org. Biomol. Chem., 2010)

(untitled) - Szaro, L. (Thin Solid Films, 1986)

(untitled) - Tsiulyanu, D.; Stratan, I.; Tsiulyanu, A.; Liess, H.-D.; Eisele, I. (Sens. Actuators, B, 2007)

(untitled) - Tsiulyanu, D.; Marian, S.; Miron, V.; Liess, H.-D. (Sens. Actuators, B, 2001)

(untitled) - Siciliano, T.; Filippo, E.; Genga, A.; Micocci, G.; Siciliano, M.; Tepore, A. (Sens. Actuators, B, 2009)

(untitled) - Bianchetti, M. F.; Heredia, E.; Oviedo, C.; Walsöe de Reca, N. E. (J. Argent. Chem. Soc., 2005)

(untitled) - Sen, S.; Muthe, K. P.; Joshi, N.; Gadkari, S. C.; Gupta, S. K.; Jagannath; Roy, M.; Deshpande, S. K.; Yakhmi, J. V. (Sens. Actuators, B, 2004)

(untitled) - Sen, S.; Bhandarkar, V.; Muthe, K. P.; Roy, M.; Deshpande, S. K.; Aiyer, R. C.; Gupta, S. K.; Yakhmi, J. V.; Sahni, V. C. (Sens. Actuators, B, 2006)

(untitled) - Tsiulyanu, D.; Marian, S.; Liess, H.-D. (Sens. Actuators, B, 2002)

(untitled) - Wang, S.; Wen, H.; Guan, W.; Zhang, L.; Ma, D.; Huang, S.; Wang, J. (Thin Solid Films, 2010)

(untitled) - Liang, F.; Qian, H. (Mater. Chem. Phys., 2009)

(untitled) - Ma, J.; Liu, X.; Wu, L.; Zheng, W. (Cryst. Res. Technol., 2008)

(untitled) - Rheem, Y.; Chang, C. H.; Hangarter, C. M.; Park, D. Y.; Lee, K. H.; Jeong, Y. S.; Myung, N. V. (Electrochim. Acta, 2010)

(untitled) - Thiebaud, L.; Legeai, S.; Stein, N. (Electrochim. Acta, 2016)

(untitled) - Sen, S.; Bhatta, U. M.; Kumar, V.; Muthe, K. P.; Bhattacharya, S.; Gupta, S. K.; Yakhmi, J. V. (Cryst. Growth Des., 2008)

(untitled) - Tsiulyanu, D.; Marian, S.; Liess, H.-D.; Eisele, I. (Sens. Actuators, B, 2004)

(untitled) - Bhandarkar, V.; Sen, S.; Muthe, K. P.; Kaur, M.; Kumar, M. S.; Deshpande, S. K.; Gupta, S. K.; Yakhmi, J. V.; Sahni, V. C. (Mater. Sci. Eng., B, 2006)

(untitled) - Tsiulyanu, D.; Marian, T.; Tiuleanu, A.; Liess, H.-D.; Eisele, I. (Thin Solid Films, 2009)

(untitled) - Her, Y. C.; Huang, S. L. (Nanotechnology, 2013)

(untitled) - Kumar, V.; Sen, S.; Sharma, M.; Muthe, K. P.; Jagannath; Gaur, N. K.; Gupta, S. K. (J. Nanosci. Nanotechnol., 2009)

(untitled) - Wang, Z.; Wang, L.; Huang, J.; Wang, H.; Pan, L.; Wei, X. (J. Mater. Chem., 2010)

(untitled) - Siciliano, T.; Di Giulio, M.; Tepore, M.; Filippo, E.; Micocci, G.; Tepore, A. (Sens. Actuators, B, 2008)

ICTEI-2015: International Conference on Telecommunications, Electronics and Informatics. Proceedings - Ciobanu, M.; Tsiulyanu, D. (Electric conductivity of tellurium-based chalcogenides thin films with Au and Ag contacts, 20.5.2015-23.5.2015, 2015)

(untitled) - Ciobanu, M.; Tsiulyanu, D. (Chalcogenide Lett., 2018)

Proceedings 6th International Conference on Telecomunications, Electronics and Informatics - Tsiulyanu, D.; Mocreac, O. (Impedance characterization of Te based gas sensitive films, 2018)

(untitled) - Tsiulyanu, D.; Ciobanu, M. (Glass Phys. Chem., 2019)

Nanoscience Advances in CBRN Agents Detection, Information and Energy Security - Tsiulyanu, D.; Moraru, A. (Nanocrystalline Tellurium Films: Fabrication and Gas Sensing Properties, 2015)

Electronic processes in non-crystalline materials - Mott, N. F.; Davis, E. A. (Clarendon Press, 1979)

Electronic Processes on Semiconductor Surfaces During Chemosorption - Wolkenstein, T. (Consultants Bureau, 1987)

Contacts and surface phenomena in quaternary glassy chalcogenides based on S and Te - Ciobanu, M. (Technical University of Moldova, 2018)

(untitled) - Mamontova, T. N.; Kochemirovskii, A. S.; Pivovarova, L. V. (Phys. Status Solidi A, 1988)

(untitled) - Tsiulyanu, D.; Mocreac, O. (Sens. Actuators, B, 2013)